Diagnostic test accuracy of self-reported frailty screening instruments in identifying community-dwelling older people at risk of frailty and pre-frailty: a systematic review protocol. (October 2017) - Ambagtsheer, Rachel C.; Thompson, Mark Q.; Archibald, Mandy M.; Casey, Mavourneen G.; Schultz, Timothy J.
Abstract : Review question/objective: : The question of this systematic review is: What is the diagnostic test accuracy of self-reported frailty screening instruments among community-dwelling older people against any of the following reference standard tests: the frailty phenotype, frailty index and comprehensive geriatric assessment?